Diverging Trends in Aggregate and Firm Volatility - Comin, Diego; Mulani, Sunil (The Review of Economics and Statistics, 2006)
This note documents the diverging trends in volatility of the growth rate of sales at the aggregate and firm levels. We establish that the upward trend in firm volatility is not simply driven by a compositional bias in the sample studied.We argue that this new fact brings into question the proposed explanations for the decline in aggregate volatility and that, given the symmetry of the diverging trends at the micro and macro levels, a common explanation is likely. We conclude by describing one such theory.